Geoelectrical soil mapping for subsurface hydrocarbon contaminant characterization and remediation site zoning at Alode, Central Niger Delta, Nigeria - Ahmed, Nurudeen Onomhoale; Nik Daud, Nik Norsyahariati; Okunlola, Ipoola Ajani (Elsevier, 2024)
Hydrocarbon impacts on subsurface environmental systems occur due to leaked buried pipelines, petroleum facilities sabotage and oil spills during exploration, production, and transportation. 2D geoelectric investigation was carried out on soils of hydrocarbon impacted site in Alode community, Eleme Local Government Area of Rivers State, Central Niger Delta, Nigeria. This was imperative due to the right-of-way spill along a sabotaged petroleum flow line that has been identified for remediation. This study employed a PASI 16 GL earth resistivity meter for Electrical Resistivity Tomography (ERT) with established 5 Wenner-4 electrode array survey lines consisting of 290 horizontal electrical profiles (HEP) probes. The survey was done in a grid format over 100 m lines at 1.5 m, 3 m, 6 m, 9 m, 12 m, and 15 m constant spacing to acquire high-resolution 2D geoelectric data. ERT data inversion was performed using GS RES2DINV and AGI Earth Imager software's to generate 2D resistivity subsurface imageries to map and delineate the hydrocarbon contaminations. The results showed resistivity values from 600 Ω-m to above 3500 Ω-m denoted impacted areas, extending beyond the maximum target depth of 6 m, as pertinent for soil excavation procedure during ex-situ remediation within the locality. ERT profiles displayed evident spill geometries at lines 1, 2 and 3 with only significant presence from below 2 m at lines 4 and 5. The result confirms the horizontal direction and vertical trajectory of the spill through a porous medium-grained sandy layer, providing information for impacted area zoning, conducting risk assessments, and designing and implementing appropriate remediation actions.